The Influence of Interpersonal Communication on Employee Performance in Public Accountants in South Jakarta - Yulianto, Wahyudi; Irawan, Pristanto Ria; Diana, Nur (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
At the South Jakarta Public Accounting Firm, the interpersonal communication implemented focuses more on open dialogue. This approach encourages self-disclosure, which often results in better feedback and understanding between employees. This strategy is implemented as an effort to improve employee performance. This research aims to analyze the impact of interpersonal communication on employee performance at the South Jakarta Public Accounting Firm. Using quantitative descriptive methods, data was collected through questionnaires and literature studies. The research sample included 62 employees, selected using the saturated sampling method. Data analysis was carried out using simple linear regression techniques. Research findings show that there is a significant influence between interpersonal communication and employee performance at the South Jakarta Public Accounting Firm. Interpersonal communication is proven to have a strong impact on employee performance. It is hoped that the results of this study can provide a valuable contribution to further research in the field of organizational communication and performance management